Development of Guidance and Counseling Media in the Form of Macro Flash Media to Increase Learning Motivation - Ardareja, Wahyu Odhip; Suriswo, Suriswo; Sudibyo, Hanung (Journal of English Language and Education, 2025)
The purpose of this study was to develop teaching media in the form of Macromedia Flash to Improve Learning Motivation of Junior High School Students in Brebes Regency. The method used was the RND method. The results of the study showed that this learning media was feasible to use based on the assessment of Guidance and Counselling practitioners with an average score of 3.00 in the good category. Expert assessment showed an overall score of 2.92, which was in the good category. The trial on students showed the following results: individual trials with an average score of 3.91 (good), small group trials with a score of 3.31 (very good), and field trials with a score of 3.26 (very good). Overall, the media scored 3.23, which was in the very good category. This media has also proven effective in improving student learning motivation based on the gain score of the increase in pre-test and post-test results. The class that used the media obtained a gain score of 0.46 (moderate category), while the class that did not use the media only reached 0.28 (low category). Thus, Macromedia Flash-based Guidance and Counselling Learning Media is declared feasible and effective for use in BK learning for class VIII.